The glance of the eye : Heidegger, Aristotle, and the ends of theory - McNeill, William, 1961- (SUNY series in contemporary continental philosophy., 1999)
"William McNeill explores the phenomenon of the Augenblick, or "glance of the eye," in Heidegger's thought, and in particular its relation to the primacy of seeing and of theoretical apprehending (theoria) both in Aristotle and in the philosophical and scientific tradition of Western thought. McNeill argues that Heidegger's early reading of Aristotle, which identifies the experience of the Augenblick at the heart of ethical and practical knowledge (phronesis), proves to be a decisive encounter for Heidegger's subsequent understanding and critique of the history of philosophy, science, and technology. It provides him with a critical resource for addressing the problematic domination of theoretical knowledge in Western civilization. Such knowledge, the author shows, always remains in a peculiar tension (itself historically determined and changing) with ethical or "protoethical" knowledge, which is bound to the finite, "ecstatic" temporality of the lived and living moment, and inevitably exposed to the presence of the sensuous."--Jacket